(untitled) (Research, Society and Development, 2021)
The article aims to present reflections on the Brazilian Psychiatric Reform, its historical trajectory and its current challenges, incorporating the understanding that it can be conceptualized as a civilizing process, respecting the citizenship rights of people in mental suffering and not just as a change of structure or health institution. This is a reflection article, with sessions that address important aspects in this context, such as psychosocial rehabilitation, harm reduction and the promotion of mental health care. Faced with a scenario in which the advances achieved in the three decades of the Psychiatric Reform in Brazil seem to be in a process of setback, showing a trend of (re)manicomialization of mental health care, it is emphasized that collective awareness is necessary, promoting a more expanded and humanized mental health care, fighting stigma and prejudice and claiming the achievements of the reform, through continuous social movements.